Dynamique successionnelle de la végétation au sein de la plaine alluviale d'une rivière semi-aride : l'exemple de l'oued Ziatine (Tunisie) - Brahim Jaziri; Hamouda Samaali (Physio-Géo, 2014)
In its downstream portion, the Ziatine wadi presents an intersected meander in the sixties, following a brutal hydrological event. The study of this sector and the related coastal area is based on cartographic and photographic documents, the oldest dating back to 1897. On this stretch, which is 4 km long, the stream has witnessed important lateral migrations. In the upstream portion of the meander, which does not flow anymore, the channel has been filled and there exist some periodic ponds. Everywhere, the shoreline vegetation is subject to the effects of the stream meandering tendencies. Between 1948 and 2007, the riparian and rush-bed areas remained stable; the lawn decreased by 11 %, but remains the largest one. The mattoral has regressed, but tree planting, especially on the coastal dune, has expanded. Cultivated spaces have remained very limited. In the future, the changes will be influenced by the dam for irrigation which was operational in 2010 in the upstream of the study area.